2023
DOI: 10.1021/acs.jchemed.2c01060
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Science Teaching in Atmospheric Ice Nucleation Research: Immersion Freezing Experiments

Abstract: This paper introduces hands-on curricular modules integrated with research in atmospheric ice nucleation, which is an important phenomenon potentially influencing global climate change. The primary goal of this work is to promote meaningful laboratory exercises to enhance the competence of students in the fields of science, technology, engineering, and math (STEM) by applying an appropriate methodology to laboratory ice nucleation measurements. To achieve this goal, three laboratory modules were developed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The lowest calculated n INP was reported at each 0.5 °C increment to prevent overestimation of n INP (Vepuri et al, 2021). Our HPLCgrade water is virtually INP-free at −25 °C (Wilbourn et al, 2023a). Data from WT-CRAFT have a minimum INP detection limit of 0.001 L −1 .…”
Section: Collection Of Aerosol Particles On Filters For Offline Inp A...mentioning
confidence: 86%
“…The lowest calculated n INP was reported at each 0.5 °C increment to prevent overestimation of n INP (Vepuri et al, 2021). Our HPLCgrade water is virtually INP-free at −25 °C (Wilbourn et al, 2023a). Data from WT-CRAFT have a minimum INP detection limit of 0.001 L −1 .…”
Section: Collection Of Aerosol Particles On Filters For Offline Inp A...mentioning
confidence: 86%
“…Samples were diluted with HPLC-grade water 10 times or 100 times as needed, and the lowest calculated nINP was reported at each 0.5 °C increment to prevent overestimation of nINP (Vepuri et al, 2021). Our HPLC-grade water is virtually INP-free at -25 °C (Wilbourn et al, 2023). Data from WT-CRAFT has a minimum INP detection limit of 0.001 L -1 .…”
Section: Collection Of Aerosol Particles On Filters For Offline Analysismentioning
confidence: 99%
“…As well, the data from SGP can be compared with previously collected nINP(T) data as reported by DeMott et al (2015) for April-June 2014 and Knopf et al (2021) for October 2019, where it becomes apparent that the data collected in this study is comparable to data collected in the spring to early summer season 2014 and measurements of nINP(T) made by other online instrumentation in Fall 2019. 440 Although there are no previous studies reporting long-term nINP(T) at ENA, in Figure 4 we have compared the data to all other studies reporting nINP(T) in locations with strong Atlantic Ocean influence (Wilbourn et al, 2023;Figure S1 and references therein). The nINP(T) range for these studies is much larger than the range reported at SGP, potentially due to either difference in sample techniques or differences in nINP(T) between the seven locations.…”
Section: Online Ice-nucleating Particle Concentrationsmentioning
confidence: 99%